Advance care planning in Asian culture. (6th August 2020) - Cheng, Shao-Yi; Lin, Cheng-Pei; Chan, Helen Yue-lai; Martina, Diah; Mori, Masanori; Kim, Sun-Hyun; Ng, Raymond
Abstract: Ageing has been recognized as one of the most critically important health-care issues worldwide. It is relevant to Asia, where the increasing number of older populations has drawn attention to the paramount need for health-care investment, particularly in end-of-life care. The advocacy of advance care planning is a mean to honor patient autonomy. Since most East Asian countries are influenced by Confucianism and the concept of 'filial piety, ' patient autonomy is consequently subordinate to family values and physician authority. The dominance from family members and physicians during a patient's end-of-life decision-making is recognized as a cultural feature in Asia. Physicians often disclose the patient's poor prognosis and corresponding treatment options to the male, family member rather to the patient him/herself. In order to address this ethical and practical dilemma, the concept of 'relational autonomy' and the collectivism paradigm might be ideally used to assist Asian people, especially older adults, to share their preferences on future care and decision-making on certain clinical situations with their families and important others. In this review article, we invited experts in end-of-life care from Hong Kong, Indonesia, Japan, South Korea, Singapore and Taiwan to briefly report the current status of advance care planning in each country from policy, legal and clinical perspectives. According to the Asian experiences, we have seen different models of advance care planning implementation. The Asian Delphi Taskforce for advance care planning is currently undertaken by six Asian countries and a more detailed, culturally sensitive whitepaper will be published in the near future. Abstract : The advocacy of Advance Care Planning (ACP) is a means to honor patient autonomy. Since most East Asian countries are influenced by the Confucianism and the concept of ``filial piety'', patient autonomy is consequently subordinate to family values and physician authority. The dominance from family members and physicians during a patient's end-of-life decision-making is recognized as a cultural feature in Asia. In order to address this ethical and practical dilemma, the concept of `relational autonomy' and the collectivism paradigm might be ideally used to assist Asian people, especially older adults, to share their preferences on future care and decision-making on certain clinical situations with their families and important others. In this review article, we invited experts in end-of-life care from Hong Kong, Indonesia, Japan, South Korea, Singapore and Taiwan to briefly report the current status of ACP in each country from policy, legal and clinical perspectives.